ANALYSIS OF ACADEMIC STRESS LEVELS OF HIGH SCHOOL STUDENTS - Kustiani, Kemala Putri; Suhendri, Suhendri; Iffah, Leni (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2024)
Academic stress is an inequality that occurs between the demands of learning with the ability of learners. The condition of learners in a state of stress can affect learning achievement. This research aims to understand the level of academic stress experienced by high school students. This study adopts a quantitative descriptive approach in research. The population that was the subject of this research consisted of 432 eleventh grade high school. Samples were taken using the methodsimple random sampling and using the significance of Slovin provisions of 5% so that the number of samples needed was found to be 208. Standard questionnaire that has been modified fromEducational Stress Scale for Adolescent (ESSA) consists of 16 statements. From the results of research, it can be drawn a meaning that high school students face academic stress with a high level that is influenced by various indicators of data collection instruments.